2017
DOI: 10.1017/s0033291717000344
|View full text |Cite
|
Sign up to set email alerts
|

Mental health-related stigma and pathways to care for people at risk of psychotic disorders or experiencing first-episode psychosis: a systematic review

Abstract: Background. Stigma associated with mental illness can delay or prevent help-seeking and service contact. Stigmarelated influences on pathways to care in the early stages of psychotic disorders have not been systematically examined.Method. This review systematically assessed findings from qualitative, quantitative and mixed-methods research studies on the relationship between stigma and pathways to care (i.e. processes associated with help-seeking and health service contact) among people experiencing first-epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 51 publications
3
105
0
3
Order By: Relevance
“…DUP has been criticised in its suitability to measure service effectiveness as definitions vary considerably across studies and are prone to a self-report bias by patients (Norman & Malla, 2001;Register-Brown & Hong, 2014;Singh, 2007). Our waiting time measure allows us to investigate the impact of delays within the care system rather than the help-seeking behaviour of patients (Gronholm, Thornicroft, , & Evans-Lacko, 2017). Second, we consider treatment intensity during the time of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…DUP has been criticised in its suitability to measure service effectiveness as definitions vary considerably across studies and are prone to a self-report bias by patients (Norman & Malla, 2001;Register-Brown & Hong, 2014;Singh, 2007). Our waiting time measure allows us to investigate the impact of delays within the care system rather than the help-seeking behaviour of patients (Gronholm, Thornicroft, , & Evans-Lacko, 2017). Second, we consider treatment intensity during the time of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have assessed this relationship specifically in first-episode psychosis (FEP), with a substantial proportion of literature being qualitative (Anderson, Fuhrer, & Malla, 2013;Chen, Gearing, DeVylder, & Oh, 2014;Connor et al, 2016;Ferrari et al, 2015;Stewart, 2013;Welsh & Tiffin, 2012). A recent systematic review of mental-health stigma and pathways to care in FEP or at-risk populations revealed only nine quantitative articles with no study exploring the relationship between stigma and help-seeking from a patient perspective in FEP (Gronholm, Thornicroft, Laurens, & Evans-Lacko, 2017). Much of the literature was found to focus on family members or carers viewpoints (Compton & Esterberg, 2005) or on atrisk populations (Rüsch & Thornicroft, 2014;Xu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A cross-national analysis of over 30 000 people found 1 in 20 adults report "psychotic-like" experiences, such as hearing voices (McGrath et al, 2015) while, in children, a larger proportion have such subclinical experiences (Fisher et al, 2013;Garralda, 2016). Data from mental health campaigns in England reveal that psychosis is challenging to destigmatize (Evans-Lacko, Corker, Williams, Henderson, & Thornicroft, 2014) and stigma is associated with poor outcomes for individuals with psychosis (Gronholm, Thornicroft, Laurens, & Evans-Lacko, 2017). However, a recent systematic review of definitions and assessments revealed psychotic experiences to be variously defined (Lee et al, 2016), and a recent British Psychological Society report aimed to normalize otherwise pathologized experiences such as voice hearing by highlighting a continuum of culturally varied ways that people interpret human experiences (Cooke, 2014).…”
Section: Introductionmentioning
confidence: 99%